Cobalt Chloride Alters Mitochondrial Function of In Vitro Cultured Cardiomyocytes in a Dose-dependent Manner - Bich, Pham Thi; Thu, Vu Thi (VNU Journal of Science: Natural Sciences and Technology, 2021)
This study was carried out to evaluate the effect of Cobalt chloride (CoCl 2 ) on cardiac mitochondrial function in an in vitro model. In the study, H9C2 cardiomyocytes were cultured in a medium containing different concentrations of CoCl 2 . Cell viability, cardiolipin content, mitochondrial function, and mitochondrial oxidative stress were assessed by using Cell Counting Kit-8 and suitable fluorescence kits. The obtained data show that CoCl 2 (200÷400 µM) induced cell death and decreased mitochondrial function of H9C2 cardiomyocytes. Particularly, CoCl 2 at the dose of 300 µM significantly altered the values of mitochondrial membrane potential, H 2 O 2 and O 2 - to 63.79±2.15%, 145.81±5.83% and 143.10±3.07% (of 100% control), respectively. Altogether, CoCl 2 strongly induced cardiomyocyte death via altering mitochondrial function in a dose-dependent manner.